REGIONAL SOLIDARITY IN THE DIGITAL SPACE: SEABLINGS VS KNETZ PHENOMENON ON SOCIAL MEDIA (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Social solidarity is no longer confined to shared territory, citizenship, ethnicity, religion, or race. This study shows how netizen solidarity can emerge suddenly, without command or planning. In mid-February 2026, a powerful digital regional solidarity arose among Southeast Asian netizens—from Indonesia, Malaysia, the Philippines, Vietnam, Thailand, and Singapore—as millions of X and Threads users united to attack South Korean netizens, sparking polarization that split Asian netizens into two camps: SEAblings and Knetz. Using a qualitative approach with framing and content analysis, this research examined the SEAblings–Knetz confrontation on X and Threads during a 72-hour peak escalation period. Drawing on Social Identity Theory, Solidarity Theory, Durkheim's Conflict Theory, and Social Polarization, four key posts were identified that overemphasized national identities, triggering both digital conflict and regional solidarity. Findings reveal that longstanding egoism and hostility among ASEAN nations—such as that between Indonesia and Malaysia—dissolved into a unified Southeast Asian identity against a common enemy, marked by a clear ingroup (SEAblings)–outgroup (Knetz) divide.